C86 TAKO–TSUBO SYNDROME IN PATIENTS WITH COVID–19: A SINGLE CENTRE RETROSPECTIVE CASE SERIES. (18th May 2022) - Alonzo, A; Di Fusco, S; Castello, L; Spinelli, A; Altamura, V; Mocini, D; Imperoli, G; Colivicchi, F
Abstract: Background: COVID–19 presents with a wide range of symptoms, from mild flu–like complaints to severe acute respiratory distress and cardiovascular complications. Recent literature provides some case reports of Tako–Tsubo syndrome (TTS) in COVID–19 patients. However, its prevalence, pathophysiological mechanisms and prognostic impact in this setting is unknown. Methods: We collected data of patients hospitalized for COVID–19 in our multidisciplinary COVID–19 department who had a diagnosis of TTS during hospitalization. The criteria for hospital admission were: 1) naso–pharyngeal polymerase chain reaction diagnosis of SARS–CoV–2 infection and 2) symptoms and signs of mild–moderate COVID–19 with a paO2/FIO2 ratio > 200. The period of the study covered the second and third wave of the pandemic in Italy. Results: Of 635 patients admitted to our centre, we had four cases, two males and two females, with TTS associated with COVID–19. No patient had any classical trigger for TTS except for COVID–19. Mean age was 72 years (67–81) and all patients had a diagnosis of SARS–CoV–2–related interstitial pneumonia confirmed by computed tomography. One patient was admitted to our centre after stabilization of a critical respiratory distress syndrome that required intubation. All patients showed typical apical ballooning with a transitory reduction of left ventricle (LV) systolic function. The mean LV ejection fraction (LVEF) at TTS onset was 42% (40–48%). ECG showed ST–segment elevation in two cases, while an evolution with negative T waves and long QTc was observed in all patients. All patients were treated in the intensive care unit (ICU), with a median ICU stay of 9 days. The long ICU stay duration was due to intercurrent superinfections. All patients recovered a normal LVEF before discharge. The mean value of the high–sensitivity troponin T peak was 1092 ng/L. Three patients underwent coronary angiography. One patient needed vasopressors in the acute phase. Two patients had a previous diagnosis of cognitive impairment. The time interval from hospital admission to TTS onset was 4 (2–6) days, and the time interval from COVID–19 symptom onset to TTS diagnosis was 10 (8–12) days. The mean hospital stay was 32 days (26–37). Conclusion: COVID–19 may be a trigger for TTS. Possible mechanisms to explain the contribution of COVID–19 to TTS development include the activation of the inflammatory cascade, direct myocardial injury, and stress–related conditions due to COVID–19.